Promoting Patient Safety Through Effective Health Information Technology Risk Management - Schneider, Eric C. (RAND Corporation, 2014)
Health information technology (IT) has the potential to improve the safety of health care, but if not carefully implemented, health IT can also introduce new risks and even harm. The authors of this report evaluated the efforts of 11 hospitals and ambulatory practices to use an improvement strategy and tools developed to promote safe use of health IT and to diagnose, monitor, and mitigate health IT-related safety risks.